Pelatihan Produk Hand Sanitizer Berbahan Baku Minyak Esensial Serai Sebagai Upaya Menghambat Penyebaran Covid 19 Bagi Guru-Guru Sekolah Inklusif - sri joeda andajani; Asri Wijiastuti; Endang Purbaningrum; yuliati yuliati (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2021)
This training was held with the aim of increasing the understanding of skills in producing hand sanitizers made from lemongrass essential oil as an effort to prevent the spread of Covid-19 for inclusive primary teachers. The training was done by the teachers in order to prevent the spread of Covid 19 to students with special needs. The training method applied can be seen through the following designs 1) knowing the initial conditions or input of the Inclusive primary teachers on hand sanitizer knowledge, 2) the training process in producing hand sanitizers, and 3) the expected outcomes after the training. The degree of success in increasing hand sanitizer training for teachers is the performance in producing hand sanitizer as an effort to prevent the spread of Covid-19 by presenting factual knowledge as well as the practice. These can be seen through the test results which show good and excellent. Keywords: training, hand sanitizer, lemongrass essential oil, covid-19